Implementasi Digital Marketing pada Usaha “Emdee.style” - Nurwinda, Fitriani; Erma Domos (Politeknik Kampar, 2025)
This project focuses on developing an effective digital marketing strategy for “Emdee.style,” a premium preloved fashion brand targeting young adults aged 20–40 years. The main goal is to enhance sales performance and broaden market reach. Through SWOT analysis, the study identified key strengths such as unique fashion collections and competitive pricing, weaknesses including low brand awareness, opportunities like increasing interest in sustainable fashion, and threats from strong competition. STP analysis further defined Emdee.style’s target market and positioned the brand as a high-quality preloved fashion provider. The implemented strategy emphasized creative digital content, active engagement on social media platforms (Instagram, TikTok, and Facebook), and integration with Shopee to improve accessibility and sales. Technical challenges, including limited devices and unstable internet connectivity, were addressed using Google Drive and adaptive work methods. The project demonstrates how SMEs can leverage digital marketing effectively to boost brand performance. Continuous content innovation and product improvement are recommended to maintain competitiveness and ensure long-term business growth.